Long-term mortality of persons with severe mental illness and diabetes: a population-based cohort study in Denmark. Issue 14 (24th March 2014) - Ribe, A. R.; Laursen, T. M.; Sandbaek, A.; Charles, M.; Nordentoft, M.; Vestergaard, M.
Abstract : Background: Persons with severe mental illness (SMI) have excess mortality, which may partly be explained by their high prevalence of diabetes. Method: We compared the overall and cause-specific mortality in persons with SMI and diabetes with that of the general Danish population between 1997 and 2009 by linking data from Danish national registries. Results: The cohort counted 4 734 703 persons, and during follow-up 651 080 persons died of whom 1083 persons had SMI and diabetes. Compared with the background population, the overall mortality rate ratios (MRRs) for persons with SMI and diabetes were 4.14 [95% confidence interval (CI) 3.81–4.51] for men and 3.13 (95% CI 2.88–3.40) for women. The cause-specific MRRs for persons with SMI and diabetes were lowest for malignant neoplasms (women: MRR = 1.98, 95% CI 1.64–2.39; men: MRR = 2.08, 95% CI 1.69–2.56) and highest for unnatural causes of death (women: MRR = 12.31, 95% CI 6.80–22.28; men: MRR = 7.89, 95% CI 5.51–11.29). The cumulative risks of death within 7 years of diabetes diagnosis for persons with SMI and diabetes were 15.0% (95% CI 12.4–17.6%) for those younger than 50 years, 30.7% (95% CI 27.8–33.4%) for those aged 50–69 years, and 63.8% (95% CI 58.9–68.2%) for those aged 70 years or older. Among persons suffering from both diseases, 33.4% of natural deaths were attributed to diabetes and 14% of natural deaths were attributed to the interaction between diabetes and SMI. Conclusions: Long-term mortality is high for persons with SMI and diabetes. This calls for effective intervention from a coordinated and collaborating healthcare system.